Transfusion increased skin blood flow when initially low in volume-resuscitated patients without acute bleeding - Cavalcante dos Santos, Elaine; Bakos, Péter; Orbegozo, Diego; Creteur, Jacques; Vincent, Jean-Louis; Taccone, Fabio Silvio (Frontiers in Medicine, 2023)
Background Alterations in skin blood flow is a marker of inadequate tissue perfusion in critically ill patients after initial resuscitation. The effects of red blood cell transfusions (RBCT) on skin perfusion are not described in this setting. We evaluated the effects of red blood cell transfusions on skin tissue perfusion in critically ill patients without acute bleeding after initial resuscitation. Methods A prospective observational study included 175 non-bleeding adult patients after fluid resuscitation requiring red blood cell transfusions. Using laser Doppler, we measured finger skin blood flow (SBF) at skin basal temperature (SBFBT), together with mean arterial pressure (MAP), heart rate (HR), hemoglobin (Hb), central venous pressure (CVP), lactate, and central or mixed venous oxygen saturation before and 1 h after RBCT. SBF responders were those with a 20% increase in SBFBT after RBCT. Results Overall, SBFBT did not significantly change after RBCT [from 79.8 (4.3–479.4) to 83.4 (4.9–561.6); p = 0.67]. A relative increase equal to or more than 20% in SBFBT after RBCT (SBF responders) was observed in 77/175 of RBCT (44%). SBF responders had significantly lower SBFBT [41.3 (4.3–279.3) vs. 136.3 (6.5–479.4) perfusion units; p < 0.01], mixed or central venous oxygen saturation (62.5 ± 9.2 vs. 67.3% ± 12.0%; p < 0.01) and CVP (8.3 ± 5.1 vs. 10.3 ± 5.6 mmHg; p = 0.03) at baseline than non-responders. SBFBT increased in responders [from 41.3 (4.3–279.3) to 93.1 (9.8–561.6) perfusion units; p < 0.01], and decreased in the non-responders [from 136.3 (6.5–479.4) to 80.0 (4.9–540.8) perfusion units; p < 0.01] after RBCT. Pre-transfusion SBFBT was independently associated with a 20% increase in SBFBT after RBCT. Baseline SBFBT had an area under receiver operator characteristic of 0.73 (95% CI, 0.68–0.83) to predict SBFBT increase; A SBFBT of 73.0 perfusion units (PU) had a sensitivity of 71.4% and a specificity of 70.4% to predict SBFBT increase after RBCT. No significant differences in SBFBT were observed after RBCT in different subgroup analyses. Conclusion The skin blood flow is globally unaltered by red blood cell transfusions in non-bleeding critically ill patients after initial resuscitation. However, a lower SBFBT at baseline was associated with a relative increase in skin tissue perfusion after RBCT.